Teknik Pemasaran Digital dalam Meningkatkan Penjualan Fintech Peer-to-Peer Lending pada Produk Dumi - Muhammad Raja Wandiro Cahyopramono; Diana Khuntari (Lembaga Pengembangan Kinerja Dosen, 2024)
Technological developments provide convenience in various fields, including marketing and finance. Currently, marketing can be carried out digitally by utilizing internet technology. The presence of online loans, which is a type of peer-to-peer lending financial technology (fintech), is the result of advances in financial technology. PT. Fidac Innovation Technology is a company operating in the fintech sector and has the Dumi product which provides online loans specifically for State Civil Apparatus (ASN). The purpose of this research is to determine digital marketing techniques in increasing sales of fintech peer-to-peer lending on Dumi products by using 5 (five) digital marketing techniques, namely: Search Engine Optimization (SEO), online advertising, email marketing, mobile applications, and social media marketing. Qualitative descriptive is used as a research method by collecting data through interviews with PT employees. Fidac Technology Innovation IT Design Division which carries out digital marketing, observation and documentation. The research results show that the digital marketing techniques implemented by PT. Fidac Technological Innovation by utilizing SEO, online advertising, social media marketing and mobile applications is already running well. However, Dumi's digital product marketing technique in the form of email marketing has not been implemented due to limited resources.